Accentuating Unabridged vs Abridged Audiobooks within Narrative Speech Materials - Sarmi, Ni Nyoman; Ramadhani, Sayla Nur Syahfah; Pratama, Ananda Firda; Tabi’in, Uais Alqarnie Sayyidut; Pasopati, Rommel Utungga; Yuliastuti, Anicleta (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2026)
This study examines the distinctions between unabridged and abridged audiobooks within the context of narrative speech materials, with a focus on how textual completeness influences listener comprehension, engagement, and interpretive depth. Unabridged audiobooks preserve the full linguistic and stylistic features of the original text, offering a comprehensive narrative experience that supports detailed understanding and authorial intent. In contrast, abridged audiobooks condense content to prioritize brevity and accessibility, often modifying narrative structure, pacing, and emphasis. Using a mixed-methods approach, this research analyzes selected narrative recordings across both formats, incorporating listener response data and discourse analysis to evaluate differences in retention, emotional engagement, and narrative coherence. Findings suggest that while abridged versions enhance accessibility and time efficiency, they may reduce exposure to nuanced language patterns and character development. Conversely, unabridged audiobooks provide richer linguistic input but require greater listener investment. The study underscores the importance of aligning audiobook format with communicative goals in educational and applied linguistic contexts. In conclusion, by accentuating the trade-offs between completeness and concision, this research contributes to a deeper understanding of how narrative speech materials can be optimized for diverse audiences and listening purposes.